Pengaruh Literasi Keuangan dan Inklusi Keuangan terhadap Kinerja UMKM di Kota Serang - Willy Nurhayadi; Urfanul Aulia; Rara Ananda Cahyadi (AKUNTANSI 45, 2024)
This study was conducted to determine the Influence of Financial Literacy and Financial Inclusion on the Performance of MSMEs in Serang City. The type of research is explanatory, with data collection techniques through questionnaires. The sampling technique uses a non-probability sampling technique, the sample is 81 people who are MSME Actors in Serang City. The analysis method used in this study is Quantitative Data Analysis. The results of the descriptive analysis show that Financial Literacy and Financial Inclusion and MSME Performance in Serang City are classified as good where the three variables are in the assessment scale range of 3.97-4.18. The results of the hypothesis test show that Financial Literacy has a positive and significant effect on MSME Performance. Financial Inclusion also has a positive and significant effect on MSME Performance. Financial Literacy and Financial Inclusion have a positive and significant effect on MSME Performance. The conclusion of this study is that Financial Literacy and Financial Inclusion in MSMEs in Serang City show that Financial Literacy and Financial Inclusion have a positive and significant effect on MSME Performance both partially and simultaneously.